Chemical methods in dewatering clayey slurry for land reclamation - Goh, Leonard Jia Rui (2015)
With rapid urbanisation and economic development, Singapore's need for more usable land space become more acute. Typically the fill material for land reclamation utilizes good quality fill material. However, Singapore has severe shortage of such materials. Singapore has been looking into using innovative methods to use soft marine clay as fill materials for land reclamation projects. However, these alternative materials have not been extensively used in reclamation works due to limited knowledge and slow setting rate as compared to other granular soil materials. This report presents findings of the studies on the potential of using marine clay as fill material for land reclamation. A key focus was on the efficiency of accelerating the settlement time and shortening the time along and improving soil properties by using chemical methods, as a mean to overcome the downside of marine clay as fill material. The objectives of this project were to investigate the possibility of using chemical flocculants to accelerate the slow settling rate and improving soil properties of marine clay. Polyacrylamide (PAM) was selected as the chemical flocculants in this project. A total of 3 types of PAM namely anionic, non-ionic and cationic were examined in this project. This report details the study on establishing the settling behaviour of the marine clay in the condition without chemical and under different operational parameters such as medium and filing sequences and to analyse the effects of PAM on the settling of marine clay slurry. Several laboratory-scale tests were carried out and examined. Settling column tests were conducted for slurry without the use of chemical to examine the settling rate of soil under different experiment settings. On the effects of chemical flocculants, a preliminary test was first carried out with several 1 litre beakers to examine the most suitable type and optimal dosage of chemical additives for the flocculation of clayey slurry. Ultimately, small settling column test with added chemical was carried out by using 30 of the 1-litre cylinders of various dosages and parameters to evaluate the self-weight settlement behaviour of slurry under various water contents and chemical contents. Based on the findings of this study, it was deducted that dosage of PAM addition of 0.5g/kg dry soil concentration showed the most increase in the settling rate and the lowest settlement height. However further studies are needed to fully examine which PAM and the corresponding concentration to select and potential effects of other parameters which are not considered in this project, for example pH, temperature, mixing speed as well as scaling up to assess the effectiveness of the use of chemical additives.